The Role of Extracellular Protein on the Pathogenicity of Xanthomonas campestris pv. citri - Tri Joko; Siti Subandiyah; Susamto Somowiyarjo (Universitas Gadjah Mada, 2000)
A research on the pathogenicity of Xanthomonas campestris pv. citri, the causal agent of citrus canker, has been carried out to study the growth characteristics of the pathogen on some media, physiological characteristics, and the role of extracellular protein on the bacterial pathogenicity. Extracellular protein of X. campestris pv. citri was extracted using ammonium sulfate precipitation. The extracted protein samples were electrophoresed on 10% polyacrilamide gel in the presence of sodium dodecyl sulfate at 15 mA/150 V for 1.5-2 hrs. Pathogenicity assay was conducted by infiltration of bacterial cell and extracellular protein suspension into citrus leaf tissues. The results showed that X. campestris pv. citri was able to grow well on all media. It possess specific protein with molecular weight of 25.71 KDa. Bacterial cell and extracellular protein of X. campestris pv. citri were able to produce typical symptoms of canker, while other closely related Xanthomonas campestris pathovars were only able to produce hypersensitive reaction on citrus leaves.